Psicologia ambiental em um hospital infantil: uma análise comportamental enfatizando qualidade de vida e bem-estar - Corrêa, Marcia Luiza Trindade (2006)
The objective of the present study was to investigate characteristics of the interactions between children and the garden of a children s hospital located in the city of Sao Paulo, identifying referring aspects to the quality of life and well-being. We used functional analysis, verifying the behaviors in terms of the contingency model and adopted the Environmental Psychology view that uses the interrelation person-environment as object of study. 14 children between 5 and 11 years old, from both genders, interned in the children s hospital had participated of this research. Three instruments had been used: half-structuralized interview, observation and behavioral mapping in the garden and application of a Quality of Life Scale. The combination of these three instruments allowed knowing important aspects in each child in their moment of internment in the hospital. The data had been presented in agreement with the principles of the behaviorism, through descriptive analysis. About the interviews, we detach that 12 of the 14 children had chosen the recreation place as their favorite space and 5 told they believe that making recreation activities improve their health. About the observation in the garden it can be affirmed that it was possible to identify the behaviors of the children that are functionally related and we detach the suggestions of inclusion of toys, but also more plants and flowers, denoting that the children do not only want to play, they also want to have a prettier natural environment. All the children had showed behaviors that denoted well-being during the observation in the garden and valued plants, flowers, the temperature and luminosity of the place. With the quality of life scale, we evidence the interaction necessity, because the majority of the children told they are unhappy when they are playing alone. Through the scale we can also reaffirm that the garden of the hospital is valued, therefore all the children told they are "happy" or "very happy" in it. The analysis suggests continuity to this work, we believe it s able to extend it to public hospitals, with the implementation of natural elements in those that don t have it